Religious Studies : The Key Concepts - Olson, Carl (London Routledge, 2011)
Exploring broad & recurring themes which are applicable in both eastern & western religions, cross-cultural examples are provided for each term to give a comprehensive overview of the subject.
Include Bibliography and Index.
The Key Concepts.
Keywords: Religion -- Religions--Study and teaching